Quantifying subjective uncertainty in survey expectations - Fabian Krüger; Lora Pavlova (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2020)
Several recent surveys ask for a person's subjective probabilities that the in ation rate falls into various outcome ranges. We provide a new measure of the uncertainty implicit in such probabilities. The measure has several advantages over existing methods: It is robust, trivial to implement, requires no functional form assumptions, and is well-defined for all logically possible probabilities. These advantages are particularly relevant when analyzing large scale consumer surveys. We illustrate the new measure using data from the Survey of Consumer Expectations.
Keywords: 330; Inflationserwartung; Verbraucher; Risiko; Befragung; Deutschland